Análise das capacidades cognitivas, emocionais e da tomada de decisão de atletas de futsal - Garcia, William Fernando (2011)
The aim of this study was to analyzing cognitive and emotional abilities about decision making of futsal players from Parana. It was studied 114 male futsal athletes of three divisions from Paranaense's Futsal Championship. Is was used as instruments the Evaluation of Declarative Knowledge on Soccer Protocol, the Style of Decision making in Sport Questionnaire and a semi-structured interview. Data collections were made in each city investigated through scheduled time with coaches. It was used the analysis of categorical content to analyze qualitative data, on the other hand, to analyze quantitative data it was used: the Chi-Square for Tendency Test, the Poisson Regression with robust adjust of variance, the Variance's Homogeneity Test, the ANOVA Test, the Tukey Test, the Box's M Test, the MANOVA Test. The results has shown: According to contextual subtheory, athletes used as intelligent strategy of adaption the interpersonal relationship between athletes and coaches, the selection of a new environment strategy occurred because of team's relationship difficulties and the behavior modeling occurred through conflict's resolution with conversation between the team; at experiential subtheory, the intelligent behavior was at interests and abilities to knowledge, beyond tasks repetition strategy for automation; at componential subtheory, intelligent behavior was identified by the difficulty in explaining how decision making occurs in spite of implicit learning; as performance and acquisition knowledge components, remembering another plays in the past, watching games and videos and relationship between athletes and more experienced athletes has shown the intelligent behavior. Regarding the ability of decision making tactic, younger athletes (18-22 years) showed prevalence (RP=1,23) to make worst decisions when compared to more experienced athletes (28-40 years); analyzing the technique level it was observed that those athletes who were called for Brazilian team showed prevalence (RP=4,01) to make better decisions when compared to athletes who haven't been called yet; in relation to the decision making style, it was observed that the learning commitment was the most widely adopted (p≤0,01); decisional competence realized was the second more adopted behavior (p≤0,01); in relation to key dispute it was not possible to observe any difference statistically significant to decision making style (p<0,05), in the same way decision making tactical ability has not shown any association with decision making style. Thus concludes: The sports context, experience in making tasks, knowledge process components and the learning commitment, was cognitive and emotional abilities that was demonstrated as important elements of decision making of the futsal athletes from Paraná.